Características clínicas y epidemiológicas de hidrocefalia en pacientes pediátricos del Hospital Regional de Loreto, 2020 2024 - López Souza, William Junior (2025)
Objective: To determine the clinical and epidemiological characteristics of hydrocephalus in pediatric patients at the Regional Hospital of Loreto from 2020 to 2024. Methods: A descriptive, observational, retrospective, and cross-sectional study was conducted. A total of 69 pediatric patients under 15 years of age diagnosed with hydrocephalus were included through the review of medical records. Data on age, sex, etiology, clinical manifestations, surgical intervention, and complications were identified. Results: The most frequently affected age group was children from 1 to 5 years old. There were 35 male patients and 34 female patients. Congenital etiology was the most common, accounting for 44 cases (63.8%). The most frequent signs and symptoms were an increase in head circumference, irritability, nausea, and vomiting. A total of 48 patients (69.6%) underwent surgical intervention, with ventriculoperitoneal shunt placement being the most common procedure, performed in 43 patients. Postoperative complications were observed in 47.9% of the surgically treated cases, with shunt obstruction being the most reported complication, Conclusions: Hydrocephalus predominantly affects pediatric patients between 1 and 5 years of age. The sex distribution was nearly equal. The most frequent etiological cause was congenital. A predominance of communicating hydrocephalus was observed. The main clinical manifestations were vomiting or nausea, irritability, and increased head circumference. A high rate of surgical intervention was noted, with ventriculoperitoneal (VP) shunt being the most used procedure. A significant presence of postoperative complications was identified, with shunt obstruction being the most common.